A supramolecular Cd(ii)-metallogel: an efficient semiconductive electronic device. Issue 48 (28th November 2018) - Dhibar, Subhendu; Dey, Arka; Majumdar, Santanu; Ghosh, Debasish; Mandal, Amit; Ray, Partha Pratim; Dey, Biswajit
Abstract : A supramolecular Cd(ii )-metallogel with oxalic acid in DMF medium has been achieved, and the semi-conductive characteristics such as the Schottky barrier diode nature of the metallogel were explored. Abstract : A sonication-based strategy for the synthesis of a functional supramolecular Cd(ii )-metallogel (CdA-OX) has been achieved through mixing cadmium(ii ) acetate dihydrate and oxalic acid dihydrate, a low molecular weight gelator (LMWG), in N, N -dimethyl formamide solvent at room temperature under atmospheric pressure. The mechanical properties of the supramolecular Cd(ii )-metallogel were investigated through a rheological study. The pebble-like self-assembly hierarchical architecture of the supramolecular metallohydrogel was visualized through field emission scanning electron microscopy investigations. The electrical properties of the metallogel were thoroughly examined and indicate its semiconducting nature. Based on its conducting properties, the Cd(ii )-metallogel was successfully applied to a Schottky barrier diode. Overall, this work is a novel instance of technologically challenging electronic device application of a Cd(ii )-metallogel.